Therapeutic and prophylactic management of bleeding from oesophageal and gastric varices – recommendations of the Working Group of the National Consultant for Gastroenterology - Rosołowski, Mariusz; Hartleb, Marek; Marek, Tomasz; Milewski, Janusz; Linke, Krzysztof; Wallner, Grzegorz; Dąbrowski, Andrzej; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Gastroesophageal varices are one of the most serious consequences of portal hypertension. One-third of patients with varices will develop variceal haemorrhage. Despite significant improvements in the outcomes of treatment, mortality due to bleeding from gastro-oesophageal varices still remains very high. These recommendations present optimal management of patients with non-bleeding and bleeding varices.